Hypercalciuria in Children with Monosymptomatic Nocturnal Enuresis - Mahmut Çivilibal; Ömer Sarılar; Mehmet Toptaş (Haseki Tıp Bülteni, 2014)
Aim: Nocturnal enuresis is a common problem in childhood. We aimed to evaluate the role of urinary calcium excretion in children with monosymptomatic nocturnal enuresis (MNE). Methods: This study included 60 children with MNE and 30 healthy controls. In addition to routine tests, urine density and urinary calcium levels were measured. Hypercalciuria was defined as the excess urinary calcium excretion ≥4mg/kg/day or urinary calcium/creatinine ratio ≥0.21. Results: Urinary calcium excretion was significantly higher in the enuresis group compared with the control group and the prevalence of hypercalciuria was 25% in children with enuresis. In conclusion, our study showed that hypercalciuria is an important finding of nocturnal enuresis. Conclusion: However, further studies are needed to clarify this relationship. (The Medical Bulletin of Haseki 2014; 52: 39-42)